Water-based paint with good frosted effect for glass surface and preparation method of water-based paint

By using the synergistic effect of two-component resin and modified nanofiller in aqueous glass matte coatings, a semi-interpenetrating network structure and multi-scale enhancement network are formed, which solves the problems of existing coatings in interface bonding, weathering and matte effects, and achieves coatings with high adhesion, wear resistance and self-cleaning properties.

CN119899568APending Publication Date: 2025-04-29ZHEJIANG XINGHUI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510061252.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

When the existing water-based glass matte coatings achieve the matte effect, there are problems such as insufficient interface bonding, poor weather resistance, uneven matte effect and insufficient mechanical strength.

Method used

A two-component resin system of hydroxyethyl methacrylate-methyl methacrylate copolymer and acrylic-styrene copolymer is used to combine modified nanosilica and aminomodified montmorillonite nanofillers to form a semi-interpenetrating network structure and multi-scale reinforcement network through surface modification and multi-layer structure design.

Benefits of technology

It significantly improves the adhesion, wear resistance and weather resistance of the coating, achieving uniform matte effect and excellent self-cleaning performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005242955560000161
    Figure BDA0005242955560000161
  • Figure BDA0005242955560000171
    Figure BDA0005242955560000171
  • Figure BDA0005242955560000172
    Figure BDA0005242955560000172
Patent Text Reader

Abstract

The invention relates to the technical field of water-based coatings, in particular to a water-based coating used for glass surfaces and having a good frosted effect and a preparation method thereof.The coating comprises, by weight, 42-48 parts of hydroxyethyl methylacrylate-methyl methacrylate copolymer, 28-32 parts of acrylic acid-styrene copolymer, 2-4 parts of a defoaming agent, 1-3 parts of a defoaming agent, 1-3 parts of a defoaming agent and 1-3 parts of a defoaming agent. The invention relates to a high-adhesion polyurethane adhesive which is prepared from the following components in parts by weight: 3.3-5.3 parts of modified nano silicon dioxide, 1.7-2.7 parts of amino modified montmorillonite, 3-4.5 parts of 2, 2, 4-trimethylpentanediol diisobutyrate, 1-1.5 parts of pentaerythritol tetraacrylate, 0.5-1 part of fluorine-containing modified polysiloxane and 0.5-1 part of polyether modified polydimethylsiloxane, and the adhesive force reaches grade 0, so that the use requirement is completely met; the wear resistance is improved by more than 200%; the excellent appearance is still kept after 3000 hours of weather resistance test; the contact angle exceeds 150 degrees, and the excellent self-cleaning effect is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-based coatings, and in particular to a water-based coating with good frosting effect for glass surfaces and a preparation method thereof. Background Art

[0002] With the deepening development of energy-saving and environmental protection concepts, water-based paints have attracted widespread attention due to their low VOC emissions and environmental friendliness. In particular, water-based paints have shown great application potential in achieving frosted effects on glass surfaces. However, the existing technologies still have many difficult-to-solve technical problems in achieving frosted effects on glass surfaces.

[0003] Traditional glass frosting mainly uses physical grinding or acid etching processes, which are not only complex, but also environmentally polluting and potentially unsafe. Although existing water-based frosted coatings have solved environmental issues to a certain extent, they still face many technical bottlenecks: first, the interface bonding between the coating and the glass substrate is insufficient, and it is easy to peel off during actual use; second, the coating has poor weather resistance and is prone to yellowing and aging in the natural environment; third, the frosting effect is uneven, making it difficult to achieve the ideal optical effect; and finally, the coating's mechanical strength and wear resistance are insufficient, affecting its service life.

[0004] The root causes of these problems are: the existing technology generally adopts a single resin system, lacking an effective cross-linked network structure; the dispersion and interface bonding of nanofillers are not ideal, and the reinforcing effect cannot be exerted; the surface modification is insufficient, making it difficult to achieve lasting functionality; the multi-layer structure design is not reasonable, and the synergy between the functional layers is poor. Therefore, it is urgent to develop a new water-based glass frosted coating system. Summary of the invention

[0005] In view of the above problems, the present invention proposes an innovative water-based coating with good frosting effect for glass surface and a preparation method thereof.

[0006] The object of the present invention is to provide a water-based coating with good frosting effect for glass surface, the coating comprising the following components in parts by weight:

[0007] 42-48 parts of hydroxyethyl methacrylate-methyl methacrylate copolymer, 28-32 parts of acrylic acid-styrene copolymer, 3.3-5.3 parts of modified nano-silica, 1.7-2.7 parts of amino-modified montmorillonite, 3-4.5 parts of 2,2,4-trimethylpentanediol diisobutyrate, 1-1.5 parts of pentaerythritol tetraacrylate, 0.5-1 parts of fluorine-containing modified polysiloxane, 0.5-1 parts of polyether-modified polydimethylsiloxane, wherein:

[0008] The molecular weight of the hydroxyethyl methacrylate-methyl methacrylate copolymer is 8000-12000, and the molecular weight of the acrylic acid-styrene copolymer is 15000-20000;

[0009] The particle size of the modified nano-silicon dioxide is 15-20 nm, and the interlayer distance of the amino-modified montmorillonite is 2.5-3.5 nm;

[0010] The mass fraction of fluorine atoms in the fluorine-containing modified polysiloxane is 8-12 wt %.

[0011] Specifically, the coating further comprises the following components in parts by weight: 0.2-0.5 parts of a defoamer, 0.3-0.6 parts of a wetting agent, 0.5-1 parts of a leveling agent, and 0.5-1 parts of a thickener.

[0012] Specifically, the preparation method of the amino-modified montmorillonite comprises the following steps: (1) reacting natural montmorillonite with a sodium carbonate solution having a concentration of 4-6wt% at 80-90°C for 4-6h to obtain sodium-based montmorillonite; (2) reacting the sodium-based montmorillonite obtained in step (1) with γ-aminopropyltriethoxysilane at 75-85°C for 3-5h, wherein the mass ratio of γ-aminopropyltriethoxysilane to sodium-based montmorillonite is 0.15-0.25:1; (3) filtering the reaction product, washing it with deionized water until it is neutral, drying it, and grinding it to obtain amino-modified montmorillonite.

[0013] Specifically, the defoaming agent is a polyether-modified polysiloxane copolymer, the wetting agent is polyoxyethylene ether-modified heptamethyltrisiloxane, the leveling agent is polydimethylsiloxane, and the thickener is a polyurethane associative thickener.

[0014] Specifically, the mass ratio of hydroxyethyl methacrylate to methyl methacrylate in the hydroxyethyl methacrylate-methyl methacrylate copolymer is 1:(1.2-1.8), and the mass ratio of acrylic acid to styrene in the acrylic acid-styrene copolymer is 1:(0.8-1.2).

[0015] The preparation method of the water-based coating comprises the following steps:

[0016] (1) Pre-dispersion step: Disperse the modified nano-silica and amino-modified montmorillonite in deionized water, shear and disperse for 20-30 min at 45-50° C. and 2000-3000 rpm, and simultaneously evacuate to -0.05 MPa;

[0017] (2) Main reaction step: adding hydroxyethyl methacrylate-methyl methacrylate copolymer and acrylic acid-styrene copolymer to the dispersed system obtained in step (1) in sequence, and stirring and reacting at 55-60° C. under nitrogen protection for 60-90 minutes;

[0018] (3) Additive adding step: cool to 45-50° C., add 2,2,4-trimethylpentanediol diisobutyrate, pentaerythritol tetraacrylate, fluorine-modified polysiloxane and polyether-modified polydimethylsiloxane in sequence, and stir for 30-40 minutes;

[0019] (4) Adjustment step: adjust the pH value to 7.5-8.0, and add deionized water to adjust the solid content to 45-50 wt%.

[0020] Specifically, in step (2), the stirring rate is 800-1000 rpm.

[0021] Specifically, in step (3), the stirring rate is 500-600 rpm.

[0022] The method for preparing a frosted coating on a glass surface using a water-based paint comprises the following steps:

[0023] (1) Primer formation: evenly apply the modified epoxy primer on the glass surface and dry at 40-45°C for 10-15 minutes;

[0024] (2) Formation of transition layer: The functionalized intermediate coating is evenly coated on the surface of the base coating and dried at 45-50°C for 8-12 minutes;

[0025] (3) Main layer formation: the water-based coating is evenly coated on the surface of the transition layer and dried at 50-55° C. for 15-20 min;

[0026] (4) Formation of functional layer: evenly apply the fluorosilicone modified coating on the surface of the main layer and dry it at 55-60°C for 10-15 minutes;

[0027] (5) Formation of protective layer: The self-healing coating is evenly coated on the surface of the functional layer and dried at 60-65°C for 20-25 minutes.

[0028] Specifically, the thickness of the primer layer is 20-25 μm, the thickness of the transition layer is 15-20 μm, the thickness of the main layer is 25-30 μm, the thickness of the functional layer is 10-15 μm, and the thickness of the protective layer is 5-10 μm.

[0029] Specifically, each coating is applied by spraying, with a spraying pressure of 0.3-0.4 MPa, a spraying distance of 20-25 cm, and a spraying speed of 15-20 cm / s.

[0030] Compared with the prior art, the water-based coating with good frosting effect for glass surface and the preparation method thereof of the present invention can achieve the following beneficial effects:

[0031] The present invention has developed a new water-based coating system. This system achieves excellent comprehensive performance through molecular design and multi-component synergy:

[0032] The present invention has successfully developed a water-based glass frosted coating with excellent comprehensive performance by in-depth research on resin molecular structure design, nanofiller surface modification, multifunctional additive synergy and multilayer structure optimization. The coating adopts a two-component resin system of hydroxyethyl methacrylate-methyl methacrylate copolymer and acrylic acid-styrene copolymer, and forms a semi-interpenetrating network structure through the cross-linking reaction of hydroxyl and carboxyl groups, which significantly improves the mechanical properties of the coating. At the same time, the two-component nanofiller of modified nano-silica and amino-modified montmorillonite is introduced, and the chemical bonding and physical barrier effect after its surface modification are utilized to achieve multi-scale enhancement.

[0033] It is particularly worth mentioning that the present invention innovatively adopts a dual-functional film-forming agent system of 2,2,4-trimethylpentanediol diisobutyrate and pentaerythritol tetraacrylate. Among them, the molecular structure of 2,2,4-trimethylpentanediol diisobutyrate contains a special trimethyl substituent, which not only provides good plasticity, but also gives the coating excellent thermal stability. The four-functional structure of pentaerythritol tetraacrylate provides efficient cross-linking sites and promotes the formation of a three-dimensional network structure.

[0034] In terms of surface modification, the present invention adopts a synergistic modification strategy of fluorine-modified polysiloxane and polyether-modified polydimethylsiloxane. Through the gradient distribution of fluorine atoms and the stability of the siloxane skeleton, the long-term stability of the coating is ensured while providing excellent hydrophobicity. This unique surface design not only achieves excellent self-cleaning effect, but also brings unexpected anti-icing performance.

[0035] Through precisely controlled process parameters and innovative multi-layer structure design, the present invention successfully maximizes the synergistic effect between the components. Experimental results show that the coating exhibits excellent comprehensive performance: the adhesion reaches level 0, fully meeting the use requirements; the wear resistance is improved by more than 200%; the weather resistance test still maintains an excellent appearance after 3000 hours; the contact angle exceeds 150°, showing an excellent self-cleaning effect.

[0036] The significant improvement in these properties is due to the innovations of the present invention in multiple aspects, including molecular design, interface engineering and process optimization. It has opened up a new technical route for the development of water-based frosted glass coatings and has important theoretical value and practical application significance. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] A water-based coating for glass surface with very good frosting effect, the components of which include by weight: 42 parts of hydroxyethyl methacrylate-methyl methacrylate copolymer, 28 parts of acrylic acid-styrene copolymer, 3.3 parts of modified nano-silica, 1.7 parts of amino-modified montmorillonite, 3 parts of 2,2,4-trimethylpentanediol diisobutyrate, 1 part of pentaerythritol tetraacrylate, 0.5 parts of fluorine-containing modified polysiloxane, 0.5 parts of polyether-modified polydimethylsiloxane, 0.2 parts of defoamer, 0.3 parts of wetting agent, 0.5 parts of leveling agent, and 0.5 parts of thickener. The fluorine-containing modified polysiloxane was purchased from Hubei Co-Formula Material Technology Co., Ltd.

[0040] The molecular weight of the hydroxyethyl methacrylate-methyl methacrylate copolymer is 8000, and the mass ratio of hydroxyethyl methacrylate to methyl methacrylate is 1:1.2. The selection of such molecular weight and monomer ratio preferably enables the copolymer to have appropriate crosslinking density and flexibility, which is beneficial to improving the wear resistance and toughness of the coating.

[0041] The molecular weight of the acrylic acid-styrene copolymer is 15000, and the mass ratio of acrylic acid to styrene is 1:0.8. The introduction of the benzene ring structure in the copolymer significantly improves the weather resistance of the coating, while the acrylic acid group enhances the adhesion to the substrate.

[0042] The particle size of the modified nano-silica is 15nm, and the interlayer spacing of the amino-modified montmorillonite is 2.5nm. The synergistic effect of the two nano-fillers forms a multi-scale reinforcement network. Among them, the nano-silica forms a chemical bond with the resin matrix through its surface silanol group, while the layered structure of the amino-modified montmorillonite provides an effective barrier effect.

[0043] The mass fraction of fluorine atoms in the fluorine-containing modified polysiloxane is 8wt%, and a gradient fluorine atom-enriched layer is formed on the surface of the coating. This special surface structure gives the coating excellent hydrophobicity and self-cleaning ability.

[0044] Preparation of amino-modified montmorillonite:

[0045] First, natural montmorillonite was reacted with a 4wt% sodium carbonate solution at 80°C for 4 hours to obtain sodium-based montmorillonite. This step increased the interlayer spacing of montmorillonite through ion exchange reaction, creating conditions for subsequent organic modification.

[0046] Then, the obtained sodium montmorillonite was reacted with γ-aminopropyltriethoxysilane (mass ratio 0.15:1) at 75°C for 3 hours. The amino end of γ-aminopropyltriethoxysilane can form a chemical bond with the resin matrix, while the silane end undergoes a grafting reaction with the surface of the montmorillonite layer, thus achieving the organic modification of the montmorillonite.

[0047] Finally, the reaction product was filtered, washed repeatedly with deionized water until the filtrate was neutral, dried at 60°C for 12 h, and ground through a 200-mesh sieve to obtain amino-modified montmorillonite.

[0048] X-ray diffraction analysis showed that the interlayer spacing of the modified montmorillonite increased from the original 1.2nm to 2.5-3.5nm, confirming the success of the organic modification. Fourier transform infrared spectroscopy showed that obvious -NH2 characteristic peaks (3380cm-1) and -CH2- characteristic peaks (2930cm-1) appeared in the modified montmorillonite, further confirming the successful grafting of aminosilane. Thermogravimetric analysis results showed that the modified montmorillonite had good thermal stability, with a decomposition temperature of more than 300℃, which fully met the subsequent processing requirements.

[0049] This modification method not only improves the compatibility of montmorillonite with organic resins, but also provides active sites for subsequent chemical bonding with the resin matrix through the introduction of amino groups, which is the key to achieving the nanofiller reinforcement effect.

[0050] The preparation method comprises the following steps:

[0051] (1) Pre-dispersion step: Disperse the modified nano-silica and amino-modified montmorillonite in deionized water, shear and disperse for 20 min at 45°C and 2000 rpm, and evacuate to -0.05 MPa. This step ensures uniform dispersion of the nanofiller and avoids agglomeration.

[0052] (2) Main reaction step: Add hydroxyethyl methacrylate-methyl methacrylate copolymer and acrylic acid-styrene copolymer to the dispersed system obtained in step (1) in sequence, and stir at 800 rpm for 60 min at 55° C. under nitrogen protection. The nitrogen protection environment can effectively prevent the occurrence of oxidation reaction and ensure the stability of the product;

[0053] (3) Additive addition step: cool to 45°C, add 2,2,4-trimethylpentanediol diisobutyrate, pentaerythritol tetraacrylate, fluorine-modified polysiloxane and polyether-modified polydimethylsiloxane in sequence, and stir at 500 rpm for 30 min. This sequential addition order of the additives ensures full compatibility of the components;

[0054] (4) Adjustment step: adjust the pH value to 7.5, add deionized water to adjust the solid content to 45 wt%. The final product exhibits excellent storage stability and construction performance.

[0055] The preparation method comprises the following steps:

[0056] (1) Pre-dispersion step: The modified nano-silica and amino-modified montmorillonite were dispersed in deionized water, and sheared and dispersed for 25 min at 47.5°C and 2500 rpm, while vacuuming to -0.05 MPa. This choice of temperature and shear rate effectively promoted the dispersion of nanoparticles, while the vacuum environment suppressed the generation of bubbles;

[0057] (2) Main reaction step: Add hydroxyethyl methacrylate-methyl methacrylate copolymer and acrylic acid-styrene copolymer to the dispersion system obtained in step (1) in sequence, and stir at 900 rpm for 75 minutes at 57.5°C under nitrogen protection. This reaction condition ensures that the resin and the nanofiller are fully combined;

[0058] (3) Additive addition step: cool to 47.5°C, add 2,2,4-trimethylpentanediol diisobutyrate, pentaerythritol tetraacrylate, fluorine-modified polysiloxane and polyether-modified polydimethylsiloxane in sequence, and stir at 550 rpm for 35 min. This mild stirring condition is conducive to the uniform dispersion of each functional additive;

[0059] (4) Adjustment step: adjust the pH value to 7.8, and add deionized water to adjust the solid content to 47.5 wt%.

[0060] The method for preparing a frosted coating on a glass surface comprises the following steps:

[0061] (1) Formation of primer layer: The modified epoxy primer is evenly coated on the glass surface and dried at 42.5° C. for 12 min. The thickness of the primer layer is 22.5 μm;

[0062] (2) Formation of transition layer: The functionalized intermediate coating is evenly coated on the surface of the base coating and dried at 47.5°C for 10 min. The thickness of the transition layer is 17.5 μm;

[0063] (3) Formation of the main layer: The water-based coating is evenly coated on the surface of the transition layer and dried at 52.5°C for 17 minutes. The thickness of the main layer is 27.5 μm;

[0064] (4) Formation of functional layer: The fluorosilicone modified coating is evenly coated on the surface of the main layer and dried at 57.5°C for 12 minutes. The thickness of the functional layer is 12.5 μm;

[0065] (5) Formation of protective layer: The self-repairing coating was evenly coated on the surface of the functional layer and dried at 62.5° C. for 22 min. The thickness of the protective layer was 7.5 μm.

[0066] Each coating was applied by spraying, with a spraying pressure of 0.35 MPa, a spraying distance of 22.5 cm, and a spraying speed of 17.5 cm / s.

[0067] Example 2

[0068] A water-based coating with excellent frosting effect for glass surface, comprising components by weight: 45 parts of hydroxyethyl methacrylate-methyl methacrylate copolymer, 30 parts of acrylic acid-styrene copolymer, 4.3 parts of modified nano-silica, 2.2 parts of amino-modified montmorillonite, 3.8 parts of 2,2,4-trimethylpentanediol diisobutyrate, 1.3 parts of pentaerythritol tetraacrylate, 0.8 parts of fluorine-containing modified polysiloxane, 0.8 parts of polyether-modified polydimethylsiloxane, 0.4 parts of defoamer, 0.5 parts of wetting agent, 0.8 parts of leveling agent and 0.8 parts of thickener.

[0069] The molecular weight of the hydroxyethyl methacrylate-methyl methacrylate copolymer is 10000, and the mass ratio of hydroxyethyl methacrylate to methyl methacrylate is 1:1.5. The selection of such a medium molecular weight optimizes the construction performance of the coating while ensuring the strength of the coating.

[0070] The molecular weight of the acrylic acid-styrene copolymer is 17500, and the mass ratio of acrylic acid to styrene is 1:1.0. This ratio not only ensures the hardness of the coating, but also provides appropriate flexibility, so that the coating has excellent comprehensive mechanical properties.

[0071] The particle size of the modified nano-silicon dioxide is 17.5 nm, and the interlayer spacing of the amino-modified montmorillonite is 3.0 nm. The medium-sized nano-filler provides better dispersibility and reinforcement effect, while the moderate interlayer spacing is conducive to the intercalation of resin molecules to form a more stable composite structure.

[0072] The mass fraction of fluorine atoms in the fluorine-containing modified polysiloxane is 10 wt %, which ensures a good surface effect without affecting the overall performance of the coating.

[0073] Preparation of amino-modified montmorillonite: Sodium-montmorillonite was prepared by reacting 5 wt % sodium carbonate solution at 85° C. for 5 h, and then reacting with γ-aminopropyltriethoxysilane (mass ratio 0.2:1) at 80° C. for 4 h. The subsequent treatment method was the same as in Example 1.

[0074] The preparation method comprises the following steps: (1) pre-dispersion step: dispersing modified nano-silica and amino-modified montmorillonite in deionized water, shearing and dispersing for 25 minutes at 47.5°C and 2500rpm, and evacuating to -0.05MPa. The selection of temperature and shear rate effectively promotes the dispersion of nanoparticles, while the vacuum environment inhibits the generation of bubbles;

[0075] (2) Main reaction step: Add hydroxyethyl methacrylate-methyl methacrylate copolymer and acrylic acid-styrene copolymer to the dispersion system obtained in step (1) in sequence, and stir at 900 rpm for 75 minutes at 57.5°C under nitrogen protection. This reaction condition ensures that the resin and the nanofiller are fully combined;

[0076] (3) Additive addition step: cool to 47.5°C, add 2,2,4-trimethylpentanediol diisobutyrate, pentaerythritol tetraacrylate, fluorine-modified polysiloxane and polyether-modified polydimethylsiloxane in sequence, and stir at 550 rpm for 35 min. This mild stirring condition is conducive to the uniform dispersion of each functional additive;

[0077] (4) Adjustment step: adjust the pH value to 7.8, and add deionized water to adjust the solid content to 47.5 wt%.

[0078] The method for preparing a frosted coating on a glass surface comprises the following steps: (1) forming a primer layer: uniformly coating the modified epoxy primer on the glass surface and drying it at 42.5° C. for 12 min. The thickness of the primer layer is 22.5 μm;

[0079] (2) Formation of transition layer: The functionalized intermediate coating is evenly coated on the surface of the base coating and dried at 47.5°C for 10 min. The thickness of the transition layer is 17.5 μm;

[0080] (3) Formation of the main layer: The water-based coating is evenly coated on the surface of the transition layer and dried at 52.5°C for 17 minutes. The thickness of the main layer is 27.5 μm;

[0081] (4) Formation of functional layer: The fluorosilicone modified coating is evenly coated on the surface of the main layer and dried at 57.5°C for 12 minutes. The thickness of the functional layer is 12.5 μm;

[0082] (5) Formation of protective layer: The self-repairing coating was evenly coated on the surface of the functional layer and dried at 62.5° C. for 22 min. The thickness of the protective layer was 7.5 μm.

[0083] Each coating was applied by spraying, with a spraying pressure of 0.35 MPa, a spraying distance of 22.5 cm, and a spraying speed of 17.5 cm / s.

[0084] Example 3

[0085] A water-based coating with excellent frosting effect for glass surface, comprising components by weight: 48 parts of hydroxyethyl methacrylate-methyl methacrylate copolymer, 32 parts of acrylic acid-styrene copolymer, 5.3 parts of modified nano silicon dioxide, 2.7 parts of amino-modified montmorillonite, 4.5 parts of 2,2,4-trimethylpentanediol diisobutyrate, 1.5 parts of pentaerythritol tetraacrylate, 1 part of fluorine-containing modified polysiloxane, 1 part of polyether-modified polydimethylsiloxane, 0.5 part of defoamer, 0.6 part of wetting agent, 1 part of leveling agent and 1 part of thickener.

[0086] The molecular weight of the hydroxyethyl methacrylate-methyl methacrylate copolymer is 12000, and the mass ratio of hydroxyethyl methacrylate to methyl methacrylate is 1:1.8. The higher molecular weight and monomer ratio give the coating a higher mechanical strength.

[0087] The molecular weight of the acrylic acid-styrene copolymer is 20000, and the mass ratio of acrylic acid to styrene is 1:1.2. The high molecular weight and high styrene content significantly improve the weather resistance and hardness of the coating.

[0088] The particle size of the modified nano-silicon dioxide is 20 nm, and the interlayer distance of the amino-modified montmorillonite is 3.5 nm. Larger nano-particles and interlayer distances provide stronger reinforcement effects.

[0089] The mass fraction of fluorine atoms in the fluorine-containing modified polysiloxane is 12 wt %, and a higher fluorine content brings about more excellent surface properties.

[0090] Sodium montmorillonite was prepared by reacting a 6 wt % sodium carbonate solution at 90° C. for 6 h, and then reacting with γ-aminopropyltriethoxysilane (mass ratio 0.25:1) at 85° C. for 5 h. The subsequent treatment method was the same as in Example 1.

[0091] The preparation method comprises the following steps:

[0092] (1) Pre-dispersion step: the modified nano-silica and amino-modified montmorillonite were dispersed in deionized water, sheared and dispersed at 50°C and 3000 rpm for 30 min, and vacuumed to -0.05 MPa;

[0093] (2) Main reaction step: hydroxyethyl methacrylate-methyl methacrylate copolymer and acrylic acid-styrene copolymer were added to the dispersed system obtained in step (1) in sequence, and stirred at 60° C. and 1000 rpm under nitrogen protection for 90 min;

[0094] (3) Additive addition step: cool to 50° C., add 2,2,4-trimethylpentanediol diisobutyrate, pentaerythritol tetraacrylate, fluorine-modified polysiloxane and polyether-modified polydimethylsiloxane in sequence, and stir at 600 rpm for 40 min;

[0095] (4) Adjustment step: adjust the pH value to 8.0, and add deionized water to adjust the solid content to 50 wt%.

[0096] The method for preparing a frosted coating on a glass surface comprises the following steps:

[0097] (1) Formation of primer layer: The modified epoxy primer is evenly coated on the glass surface and dried at 45° C. for 10 min. The thickness of the primer layer is 25 μm;

[0098] (2) Formation of transition layer: The functionalized intermediate coating is evenly coated on the surface of the base coating and dried at 50°C for 8 minutes. The thickness of the transition layer is 20 μm;

[0099] (3) Formation of the main layer: The water-based coating is evenly coated on the surface of the transition layer and dried at 55°C for 15 minutes. The thickness of the main layer is 30 μm;

[0100] (4) Formation of functional layer: The fluorosilicone modified coating is evenly coated on the surface of the main layer and dried at 60°C for 10 minutes. The thickness of the functional layer is 15 μm;

[0101] (5) Formation of protective layer: The self-repairing coating is evenly coated on the surface of the functional layer and dried at 65° C. for 20 min. The thickness of the protective layer is 10 μm.

[0102] Each coating was applied by spraying, with a spraying pressure of 0.4 MPa, a spraying distance of 25 cm, and a spraying speed of 20 cm / s.

[0103] Example 4

[0104] A water-based coating with excellent frosting effect for glass surface, comprising components by weight: 45 parts of hydroxyethyl methacrylate-methyl methacrylate copolymer, 30 parts of acrylic acid-styrene copolymer, 4.3 parts of modified nano-silica, 2.2 parts of amino-modified montmorillonite, 4.0 parts of 2,2,4-trimethylpentanediol diisobutyrate, 1.2 parts of pentaerythritol tetraacrylate, 0.7 parts of fluorine-containing modified polysiloxane, 0.7 parts of polyether-modified polydimethylsiloxane, 0.3 parts of defoaming agent, 0.4 parts of wetting agent, 0.7 parts of leveling agent and 0.7 parts of thickener.

[0105] The molecular weight of the hydroxyethyl methacrylate-methyl methacrylate copolymer is 11000, and the mass ratio of hydroxyethyl methacrylate to methyl methacrylate is 1:1.6. This medium to high molecular weight and monomer ratio achieves good processing performance while ensuring the strength of the coating.

[0106] The molecular weight of the acrylic acid-styrene copolymer is 18500, and the mass ratio of acrylic acid to styrene is 1:1.1. Preferably, this ratio provides sufficient hardness while maintaining good flexibility.

[0107] The particle size of the modified nano-silicon dioxide is 18.5 nm, and the interlayer distance of the amino-modified montmorillonite is 3.2 nm. The selection of such particle size and interlayer distance achieves the best balance between the nano-enhancement effect and the dispersibility.

[0108] The mass fraction of fluorine atoms in the fluorine-containing modified polysiloxane is 11 wt %, and this content enables the coating to have ideal surface properties.

[0109] Preparation of amino-modified montmorillonite: sodium-based montmorillonite was prepared by reacting 5.5 wt% sodium carbonate solution at 83°C for 5.5 h, and then reacting with γ-aminopropyltriethoxysilane (mass ratio 0.22:1) at 82°C for 4.5 h. The subsequent treatment method was the same as in Example 1.

[0110] The preparation method comprises the following steps:

[0111] (1) Pre-dispersion step: Disperse the modified nano-silica and amino-modified montmorillonite in deionized water, shear and disperse for 28 minutes at 48°C and 2800 rpm, and simultaneously evacuate to -0.05 MPa. This selection of process conditions effectively promotes the uniform dispersion of nanofillers;

[0112] (2) Main reaction step: Add hydroxyethyl methacrylate-methyl methacrylate copolymer and acrylic acid-styrene copolymer to the dispersion system obtained in step (1) in sequence, and stir at 950 rpm for 80 min at 58°C under nitrogen protection. Such reaction conditions ensure full compatibility and combination of the resin and the nanofiller;

[0113] (3) Additive addition step: cool to 48°C, add 2,2,4-trimethylpentanediol diisobutyrate, pentaerythritol tetraacrylate, fluorine-modified polysiloxane and polyether-modified polydimethylsiloxane in sequence, and stir at 580 rpm for 38 minutes. Preferably, such stirring conditions enable each functional additive to fully exert its synergistic effect;

[0114] (4) Adjustment step: adjust the pH value to 7.7, and add deionized water to adjust the solid content to 48.5 wt%.

[0115] The method for preparing a frosted coating on a glass surface comprises the following steps:

[0116] (1) Formation of primer layer: The modified epoxy primer was evenly coated on the glass surface and dried at 43° C. for 11 min. The thickness of the primer layer was 23 μm;

[0117] (2) Formation of transition layer: The functionalized intermediate coating is evenly coated on the surface of the base coating and dried at 48°C for 9 minutes. The thickness of the transition layer is 18 μm;

[0118] (3) Formation of the main layer: The water-based coating is evenly coated on the surface of the transition layer and dried at 53°C for 16 minutes. The thickness of the main layer is 28 μm;

[0119] (4) Formation of functional layer: The fluorosilicone modified coating is evenly coated on the surface of the main layer and dried at 58°C for 11 minutes. The thickness of the functional layer is 13 μm;

[0120] (5) Formation of protective layer: The self-repairing coating was evenly coated on the surface of the functional layer and dried at 63° C. for 21 min. The thickness of the protective layer was 8 μm.

[0121] Each coating is applied by spraying, with a spraying pressure of 0.38MPa, a spraying distance of 23.5cm, and a spraying speed of 18.5cm / s. This precise process parameter control ensures the uniformity of the coating and the full performance of its overall performance.

[0122] Through the above four embodiments, the numerical ranges of various technical features of the present invention are fully covered, and the feasibility and technical effects of the present invention are fully demonstrated. The parameter selection in different embodiments is optimized and designed, and each embodiment can achieve good frosting effect and comprehensive performance.

[0123] Comparative Example 1

[0124] For Example 1, verify the synergistic effect of the two-component resin system. A single resin is used to replace the two-component resin system, and its components include by weight: 70 parts of hydroxyethyl methacrylate-methyl methacrylate copolymer (molecular weight 8000, monomer ratio 1: 1.2), 3.3 parts of modified nano-silica, 1.7 parts of amino-modified montmorillonite, 3 parts of 2,2,4-trimethylpentanediol diisobutyrate, 1 part of pentaerythritol tetraacrylate, 0.5 parts of fluorine-containing modified polysiloxane, 0.5 parts of polyether-modified polydimethylsiloxane, 0.2 parts of defoamer, 0.3 parts of wetting agent, 0.5 parts of leveling agent, and 0.5 parts of thickener. Wherein, the defoamer is a polyether-modified polysiloxane copolymer, the wetting agent is polyoxyethylene ether-modified heptamethyl trisiloxane, the leveling agent is polydimethylsiloxane, and the thickener is a polyurethane associative thickener.

[0125] The preparation method is the same as that of Example 1. The results show that the lack of the synergistic effect of the acrylic acid-styrene copolymer significantly reduces the weather resistance of the coating, reduces the wear resistance by 40%, and shows obvious yellowing. This verifies the necessity of the two-component resin system in providing comprehensive performance.

[0126] Comparative Example 2

[0127] For Example 2, the synergistic effect of nanofillers was verified. Only 6.5 parts of modified nanosilica was used, and the amino-modified montmorillonite was removed. The other components and preparation methods were the same as in Example 2. The results showed that the barrier performance of the coating was significantly reduced without the synergistic effect of the layered montmorillonite, the anti-permeability decreased by 50%, and the surface hardness was insufficient. This confirms the importance of the two-component nanofiller system.

[0128] Comparative Example 3

[0129] The synergistic effect of the film-forming aid was verified for Example 3. Only 6 parts of 2,2,4-trimethylpentanediol diisobutyrate was used, pentaerythritol tetraacrylate was removed, and the other components and process parameters were the same as those of Example 3. The results showed that the lack of the synergistic effect of the multifunctional crosslinking agent resulted in insufficient crosslinking density of the coating, a 60% decrease in solvent resistance, and obvious softening.

[0130] Comparative Example 4

[0131] The synergistic effect of the surface regulator was verified for Example 4. Only 1.4 parts of fluorine-modified polysiloxane was used, and the polyether-modified polydimethylsiloxane was removed. The other components and process parameters were the same as those of Example 4. The results showed that the lack of the synergistic effect of siloxane resulted in uneven surface energy distribution of the coating, a 70% reduction in the self-cleaning effect, and insufficient local hydrophobicity.

[0132] Comparative Example 5

[0133] For Example 1, the criticality of process parameters was verified. The same formula was used, but the process parameters of the pre-dispersion step were changed: the temperature was reduced to 30°C, the rotation speed was reduced to 1000 rpm, and the time was shortened to 10 minutes. The results showed that the nanofiller was not evenly dispersed, resulting in serious insufficient coating performance, a 200% increase in surface roughness, and obvious agglomeration.

[0134] Comparative Example 6

[0135] For Example 2, the necessity of multi-layer structure design was verified. The same formula was used, but simplified to a three-layer structure (the functional layer and the protective layer were removed). The results showed that the durability of the coating was significantly reduced, and obvious performance degradation occurred after 3000 hours of aging, the surface hardness decreased by 45%, and the self-repair function was completely lost.

[0136] It can be clearly seen from the above comparative examples that the synergistic effect of the two-component resin system is the key to achieving high performance; the synergistic enhancement effect of nanofillers is indispensable; the multiple action mechanisms of film-forming aids significantly improve coating performance; the synergistic modification effect of surface regulators is crucial; precise control of process parameters directly affects product quality; and multi-layer structure design plays a decisive role in long-term performance stability.

[0137] These comparative results fully demonstrate the necessity and uniqueness of the various innovative features of the present invention and demonstrate significant technical effects.

[0138] A series of comprehensive performance test schemes are designed for the water-based matte coating of the present invention, as follows:

[0139] 1. Basic coating performance test

[0140] 1. Adhesion test

[0141] Test method: According to GB / T 9286-1998 standard, the cross-cut test is carried out. 100 1mm×1mm squares are scratched on the coating surface with a cross-cut knife, and then quickly peeled off after sticking with tape.

[0142] Test conditions: temperature 23±2℃, relative humidity 50±5%.

[0143] Rating standard: 0-5, 0 means no shedding at all, 5 means shedding area exceeds 65%.

[0144] 2. Wear resistance test

[0145] Test method: Taber wear tester, CS-10 grinding wheel, load 1000g.

[0146] Test conditions: continuous wear for 1000 revolutions at room temperature.

[0147] Evaluation index: mass loss (mg / 1000r).

[0148] 3. Weather resistance test

[0149] Test method: According to GB / T 1865-2009, xenon lamp aging test was used.

[0150] Test conditions: irradiance 0.55W / m 2 , blackboard temperature 63±3℃, relative humidity 50±5%. Test cycle: 3000 hours.

[0151] Evaluation index: yellowing index (ΔYI) and gloss retention rate (%).

[0152] 2. Special performance test

[0153] 1. Surface morphology analysis

[0154] Test method: Observation using atomic force microscopy (AFM).

[0155] Test conditions: tapping mode, scanning range 5μm×5μm.

[0156] Evaluation indicators: surface roughness (Ra) and morphology uniformity.

[0157] 2. Cross-link density test

[0158] Test method: Determined by swelling method.

[0159] Test conditions: Use tetrahydrofuran as solvent and soak at 25°C for 48 hours.

[0160] Evaluation index: swelling degree (%) and cross-linking density (mol / cm 3 ).

[0161] 3. Functional performance test

[0162] 1. Hydrophobicity test

[0163] Test method: Use contact angle measuring instrument.

[0164] Test conditions: room temperature, using deionized water, droplet volume 5 μL.

[0165] Evaluation indicators: static contact angle (°) and rolling angle (°).

[0166] The test results are as follows (shown in table form):

[0167] Table 1 Basic performance test results

[0168]

[0169]

[0170] Table 2 Special performance and functional performance test results

[0171]

[0172] Through the analysis of the test results, Example 3 shows the best comprehensive performance and can be determined as the best embodiment. In-depth analysis of the test data shows that the present invention has the following unexpected technical effects:

[0173] 1. Ultra-high wear resistance: Through the synergistic effect of two-component resin and nanofiller, the wear resistance is far superior to that of the existing technology, and the wear loss is only 40-50% of the comparison sample. This significant improvement is due to the multi-scale enhancement mechanism of the semi-interpenetrating network structure and nanofiller.

[0174] 2. Excellent weather resistance: After 3000 hours of accelerated aging test, the yellowing index of the embodiment is significantly lower than that of the control sample, and the gloss retention rate remains above 95%. This is due to the introduction of the benzene ring structure and the synergistic protection of fluorine and silicon.

[0175] 3. Excellent self-cleaning effect: The contact angle of the examples generally exceeds 150°, and the rolling angle is less than 5°, showing excellent superhydrophobic properties. This effect is attributed to the gradient distribution of surface fluorine atoms and the formation of a micro-nano double-layer structure.

[0176] 4. Outstanding interfacial bonding strength: The adhesion of the examples all reached level 0, showing perfect interfacial bonding performance. This is due to the multilayer structure design and the formation of a chemical bonding network.

[0177] 5. Ideal surface morphology: The surface roughness of the embodiment is controlled within the range of 125-132 nm, which is significantly better than that of the comparative sample. This precise surface structure control is derived from the optimization of process parameters and the synergistic effect of the material system.

[0178] These test results fully confirm the innovation and leading nature of the present invention in terms of material design, process optimization and performance improvement. In particular, through the synergistic effect of multiple components, a qualitative leap in performance has been achieved, providing a new technical route for the development of high-performance water-based matte coatings.

[0179] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A water-based coating with good frosting effect for glass surface, characterized in that: The coating comprises the following components in parts by weight: 42-48 parts of hydroxyethyl methacrylate-methyl methacrylate copolymer, 28-32 parts of acrylic acid-styrene copolymer, 3.3-5.3 parts of modified nano-silica, 1.7-2.7 parts of amino-modified montmorillonite, 3-4.5 parts of 2,2,4-trimethylpentanediol diisobutyrate, 1-1.5 parts of pentaerythritol tetraacrylate, 0.5-1 parts of fluorine-containing modified polysiloxane, 0.5-1 parts of polyether-modified polydimethylsiloxane, wherein: The molecular weight of the hydroxyethyl methacrylate-methyl methacrylate copolymer is 8000-12000, and the molecular weight of the acrylic acid-styrene copolymer is 15000-20000; The particle size of the modified nano-silicon dioxide is 15-20 nm, and the interlayer distance of the amino-modified montmorillonite is 2.5-3.5 nm; The mass fraction of fluorine atoms in the fluorine-containing modified polysiloxane is 8-12 wt %.

2. The water-based paint according to claim 1, characterized in that: The coating also includes the following components in parts by weight: 0.2-0.5 parts of a defoamer, 0.3-0.6 parts of a wetting agent, 0.5-1 parts of a leveling agent, and 0.5-1 parts of a thickener. The defoamer is a polyether-modified polysiloxane copolymer, the wetting agent is a polyoxyethylene ether-modified heptamethyltrisiloxane, the leveling agent is a polydimethylsiloxane, and the thickener is a polyurethane associative thickener.

3. The water-based paint according to claim 1, characterized in that: The preparation method of amino-modified montmorillonite comprises the following steps: (1) reacting natural montmorillonite with a sodium carbonate solution having a concentration of 4-6 wt % at 80-90° C. for 4-6 h to obtain sodium-based montmorillonite; (2) reacting the sodium-based montmorillonite obtained in step (1) with γ-aminopropyltriethoxysilane at 75-85° C. for 3-5 h, wherein the mass ratio of γ-aminopropyltriethoxysilane to sodium-based montmorillonite is 0.15-0.25:1; and (3) filtering the reaction product, washing it with deionized water until it is neutral, drying it, and grinding it to obtain amino-modified montmorillonite.

4. The water-based paint according to claim 1, characterized in that: The mass ratio of hydroxyethyl methacrylate to methyl methacrylate in the hydroxyethyl methacrylate-methyl methacrylate copolymer is 1:(1.2-1.8), and the mass ratio of acrylic acid to styrene in the acrylic acid-styrene copolymer is 1:(0.8-1.2).

5. The method for preparing a water-based coating according to any one of claims 1 to 4, characterized in that: The steps include: (1) Pre-dispersion step: Disperse the modified nano-silica and amino-modified montmorillonite in deionized water, shear and disperse for 20-30 min at 45-50° C. and 2000-3000 rpm, and simultaneously evacuate to -0.05 MPa; (2) Main reaction step: adding hydroxyethyl methacrylate-methyl methacrylate copolymer and acrylic acid-styrene copolymer to the dispersed system obtained in step (1) in sequence, and stirring and reacting at 55-60° C. under nitrogen protection for 60-90 minutes; (3) Additive adding step: cool to 45-50° C., add 2,2,4-trimethylpentanediol diisobutyrate, pentaerythritol tetraacrylate, fluorine-modified polysiloxane and polyether-modified polydimethylsiloxane in sequence, and stir for 30-40 minutes; (4) Adjustment step: adjust the pH value to 7.5-8.0, and add deionized water to adjust the solid content to 45-50 wt%.

6. The preparation method according to claim 5, characterized in that: In step (2), the stirring rate is 800-1000 rpm.

7. The preparation method according to claim 5, characterized in that: In step (3), the stirring rate is 500-600 rpm.

8. The method for preparing a frosted coating on a glass surface using a water-based paint according to any one of claims 1 to 4, characterized in that: The steps include: (1) Primer formation: evenly apply the modified epoxy primer on the glass surface and dry at 40-45°C for 10-15 minutes; (2) Formation of transition layer: evenly apply the functionalized intermediate coating on the surface of the base coating and dry it at 45-50°C for 8-12 minutes; (3) Main layer formation: the water-based coating is evenly coated on the surface of the transition layer and dried at 50-55° C. for 15-20 min; (4) Formation of functional layer: evenly apply the fluorosilicone modified coating on the surface of the main layer and dry it at 55-60°C for 10-15 minutes; (5) Formation of protective layer: The self-healing coating is evenly coated on the surface of the functional layer and dried at 60-65°C for 20-25 minutes.

9. The method according to claim 8, characterized in that The thickness of the primer layer is 20-25 μm, the thickness of the transition layer is 15-20 μm, the thickness of the main layer is 25-30 μm, the thickness of the functional layer is 10-15 μm, and the thickness of the protective layer is 5-10 μm.

10. The method according to claim 8, characterized in that Each coating is applied by spraying, with a spraying pressure of 0.3-0.4 MPa, a spraying distance of 20-25 cm, and a spraying speed of 15-20 cm / s.